Changes in Liver Function Test During Intensive Phase of Anti-Tuberculosis Treatment - Mansoor , Javeria; Azam , Muhammad; Fazal ur Rehman; Mansoor , Nadia; Manzoor , Rida; Khan , Khushhal; Inamullah; Shah , Syed Nadir (Indus Journal of Bioscience Research, 2025)
Background: Anti-tuberculosis treatment (ATT) has the potential to be hepatotoxic, particularly during the intense phase. It is crucial to keep an eye on liver function tests (LFTs) at this time to avoid problems and guarantee treatment compliance. Objective: To evaluate how liver function test parameters vary in individuals receiving anti-tuberculosis therapy during the intensive phase of treatment. Methodology: A total of 120 patients were included in the two-month intense phase of ATT. Both at baseline and two months later, bilirubin levels and liver enzymes (ALT, AST, and ALP) were measured. In order to collect information on liver dysfunction symptoms, such as fatigue, jaundice, nausea, and stomach pain, patient interviews were also undertaken. A qualitative theme approach was employed in the study to examine patient awareness and experiences. Results: ALT and AST levels increased significantly after the intensive period, going from 34 U/L to 88 U/L and from 30 U/L to 76 U/L, respectively. Abdominal discomfort (17%), nausea (47%), jaundice (21%), exhaustion (60%), and loss of appetite (53%), were among the clinical complaints recorded. Qualitative results showed delayed symptom reporting and low awareness. Conclusion: The results showed a notable increase in liver enzymes during the anti-tuberculosis treatment’s intensive phase, suggesting possible liver impairment. Fatigue, nausea, and jaundice were among the frequently reported symptoms, highlighting the significance of keeping an eye on liver function during therapy to avoid problems